Design analysis of radial flux dual stator five phase permanent magnet synchronous generator - Kumar R.R.; Singh S.K.; Srivastava R.K. (My University, 2025)
Recent advancement in permanent magnet synchronous generator (PMSG) is pushing the industry towards cost effective, reliable, high power density, echo friendly solutions. The dual stator multiphase radial flux PMSG has the potential to meet these expectations. The prime focus of this paper is to design a low power dual stator multiphase radial flux PMSG for extraction of wind power in remote areas. The reluctance network model (RNM) based analytical approach proposed for this specific machine is the novelty of this paper. Furthermore, this analytical model is validated using finite element method (FEM). Based on these methods, the performance parameters in terms of generated emf and air gap magnetic flux density is estimated. Efforts have been made to minimize the leakage flux using asymmetrical magnet structure for the inner and the outer permanent magnets. The inner stator and the outer stator induced voltage, using power electronic converter would allow voltage regulation under variable load and variable wind conditions. © 2014 IEEE.